Acute and subacute toxicity evaluation of Houttuynia cordata ethanol extract and plasma metabolic profiling analysis in both male and female rats. Issue 12 (31st May 2021) - Chen, Hongjiang; Sha, Xiuxiu; Luo, Yiyuan; Chen, Jianwei; Li, Xiang; Wang, Juan; Cao, Gang; Peng, Xin
Abstract: Houttuynia cordata has been used as a traditional medicine for more than 1500 years. It has aroused wide public concern about its safety in the past few years, for it contains various aristolactams. However, the safety of H. cordata extract remains unclear. In the present study, single dose (2000 mg/kg) and subacute (250, 500, and 1000 mg/kg/day for 28 days) oral toxicity studies of the 95% ethanol extract of H. cordata (HCE) were performed in both male and female Sprague–Dawley (SD) rats. Hematological, biochemical, histopathological parameters, and plasma metabolic profiling were assessed. The single‐dose toxicity of HCE was more than 2000 mg/kg. The subacute toxicity results showed that no significant adverse effect of HCE was observed at 250 mg/kg/day. However, five rats died in 500 and 1000 mg/kg/day groups and exhibited toxicities to liver and kidney. Plasma metabolic profiling analysis suggested that a number of metabolic disturbances were induced by oral administration of HCE, focusing on energy metabolism, amino acid metabolism, and lipids metabolism. Moreover, it appeared that male rats were more susceptible to the toxic effects of HCE than female rats. Therefore, in this preliminary study, oral administration of HCE 250 mg/kg/day can be regarded as the no observed adverse effect level in rats over 28 days. However, long‐term use of HCE with large doses exhibited some hepatotoxicity and nephrotoxicity in rats. Abstract : In this preliminary study, oral administration of the ethanol extract of Houttuynia cordata (HCE) 250 mg/kg/day can be regarded as the no observed adverse effect level in rats over 28 days. However, long‐term use of HCE with large doses exhibited some hepatotoxicity and nephrotoxicity in rats.